2018
DOI: 10.1111/psyp.13309
|View full text |Cite
|
Sign up to set email alerts
|

The reality of “food porn”: Larger brain responses to food‐related cues than to erotic images predict cue‐induced eating

Abstract: While some individuals can defy the lure of temptation, many others find appetizing food irresistible. The goal of this study was to investigate the neuropsychological mechanisms that increase individuals' vulnerability to cue‐induced eating. Using ERPs, a direct measure of brain activity, we showed that individuals with larger late positive potentials in response to food‐related cues than to erotic images are more susceptible to cue‐induced eating and, in the presence of a palatable food option, eat more than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 78 publications
6
27
2
Order By: Relevance
“…With regard to baseline levels of brain activity predicting overall changes in food liking, craving, and consumption over the course of the 6 month follow-up period, we did not find any evidence that brain activity during food cue reactivity predicted behavior changes in the domains of unhealthy or healthy foods. These results are contrary to much of the previous findings in this domain, which have shown relatively consistent associations between food cue reactivity and behavior change using dependent variables such as weight gain/loss, cue-induced eating, or snack consumption (e.g., Demos et al, 2012 ; Lawrence et al, 2012 ; Murdaugh et al, 2012 ; Versace et al, 2018 ). The present null result may be due to the paradigm we used to index food cue reactivity, which contrasted two energy-dense foods that only differed based on participant preference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With regard to baseline levels of brain activity predicting overall changes in food liking, craving, and consumption over the course of the 6 month follow-up period, we did not find any evidence that brain activity during food cue reactivity predicted behavior changes in the domains of unhealthy or healthy foods. These results are contrary to much of the previous findings in this domain, which have shown relatively consistent associations between food cue reactivity and behavior change using dependent variables such as weight gain/loss, cue-induced eating, or snack consumption (e.g., Demos et al, 2012 ; Lawrence et al, 2012 ; Murdaugh et al, 2012 ; Versace et al, 2018 ). The present null result may be due to the paradigm we used to index food cue reactivity, which contrasted two energy-dense foods that only differed based on participant preference.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, physiological and neural responses to food cues are also prospectively associated with both eating behavior and weight gain ( Rogers and Hill, 1989 ; Nederkoorn et al, 2000 ; Nederkoorn and Jansen, 2002 ; Jansen et al, 2003 ; Stice et al, 2010 ; Yokum et al, 2011 , 2014 ; Demos et al, 2012 ; Lawrence et al, 2012 ; Mehta et al, 2012 ; Murdaugh et al, 2012 ; Lopez et al, 2014 ; Winter et al, 2017 ; Versace et al, 2018 ). This literature, while robust, is not uniform; several studies investigating measures of food cue reactivity have failed to demonstrate associations with eating behavior and/or weight, or found an association with physiological cue reactivity but not self-reported reactivity (see Boswell and Kober, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to baseline levels of brain activity predicting overall changes in food liking, craving, and consumption over the course of the six month follow-up period, we did not find any evidence that brain activity during food cue reactivity predicted behavior changes in the domains of unhealthy or healthy foods. These results are contrary to much of the previous findings in this domain, which have shown relatively consistent associations between food cue reactivity and behavior change using dependent variables such as weight gain/loss, cue-induced eating, or snack consumption (e.g., Demos et al, 2012;Lawrence et al, 2012;Murdaugh et al, 2012;Versace et al, 2018). The present null result may be due to the paradigm we used to index food cue reactivity, which contrasted two energydense foods that only differed based on participant preference.…”
Section: Reactivitycontrasting
confidence: 99%
“…Similarly, physiological and neural responses to food cues are also prospectively associated with both eating behavior and weight gain (Demos et al, 2012;Jansen et al, 2003;Lawrence et al, 2012;Lopez et al, 2014;Mehta et al, 2012;Murdaugh et al, 2012;Nederkoorn et al, 2000;Nederkoorn & Jansen, 2002;Rogers & Hill, 1989;Stice et al, 2010;Versace et al, 2018;Winter et al, 2017;Yokum et al, 2011Yokum et al, , 2014. This literature, while robust, is not uniform; several studies investigating measures of food cue reactivity have failed to demonstrate associations with eating behavior and/or weight, or found an association with physiological cue reactivity but not self-reported reactivity (see Boswell & Kober, 2016).…”
Section: Behavior Change From Food Cue Reactivitymentioning
confidence: 99%
“…35 According to previous studies, some individuals are more susceptible to cue-induced eating in the presence of a palatable food option. 36 Other studies have suggested that an increased attentional bias to food cues may contribute to overeating and weight gain. 37 39 In particular, given the content of mukbang YouTube videos, long-term research is needed on the effect of mukbang.…”
Section: Discussionmentioning
confidence: 99%